2005
DOI: 10.1159/000087705
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Units, Tissue Plasminogen Activator, Aspirin and Neuroprotection: Which Stroke Intervention Could Provide the Greatest Community Benefit?

Abstract: Background: Although a number of acute stroke interventions are of proven efficacy, there is uncertainty about their community benefits. We aimed to assess this within a defined population. Methods: Eligibility for tissue plasminogen activator (tPA), aspirin, stroke unit management and neuroprotection were assessed among incident stroke cases within the community-based North East Melbourne Stroke Incidence Study. Results: Among 306,631 people, there were 645 incident strokes managed in hospital. When eligible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 29 publications
1
44
0
8
Order By: Relevance
“…7 Among these interventions, the stroke unit effect has potentially the greatest population impact as it combines both moderate effectiveness and broad applicability. 1,2 However, as it is a complex intervention it is difficult to be certain about the key components of stroke unit care. 8 Descriptive studies have reported that early mobilisation (EM) (starting out of bed, sitting, standing and walking early after stroke) is widely thought to be an important contributor to the stroke unit effect.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…7 Among these interventions, the stroke unit effect has potentially the greatest population impact as it combines both moderate effectiveness and broad applicability. 1,2 However, as it is a complex intervention it is difficult to be certain about the key components of stroke unit care. 8 Descriptive studies have reported that early mobilisation (EM) (starting out of bed, sitting, standing and walking early after stroke) is widely thought to be an important contributor to the stroke unit effect.…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…Currently, evidence-based treatments, such as thrombolysis within 3 hours, aspirin, and admission to stroke units, are more commonly used for patients with acute stroke. [26][27][28][29][30] Our study shows that the proportion of patients with ischemic stroke receiving thrombolytic treatment significantly increased from 1.4% to 3.9% after the intervention in the intervention communities. Moreover, more patients with stroke received antithrombotic and lipidlowering agents at postintervention.…”
Section: Discussionmentioning
confidence: 83%
“…Stroke patients should be treated in stroke unit [10][11][12][33][34][35][36] , since recent studies have supported the effectiveness of stroke units and management in a stroke rehabilitation unit confers survival benefits 10 years after stroke, probably because long-term survival is related to early reduction in disability 35 . An estimate based on data obtained from the North East Melbourne Stroke Incidence Study showed that although t-PA was the most potent intervention, the management in stroke units had the greatest population benefit 36 .…”
Section: Stroke Unitsmentioning
confidence: 99%
“…An estimate based on data obtained from the North East Melbourne Stroke Incidence Study showed that although t-PA was the most potent intervention, the management in stroke units had the greatest population benefit 36 . Stroke unit care, as provided in routine clinical practice in United Kingdom 37 and Sweden [38][39][40] , is associated with reduced case fatality by up to 25%, and reduction in mortality by 46% compared with general ward treatment 41 .…”
Section: Stroke Unitsmentioning
confidence: 99%